PERLINDUNGAN HUKUM TERRHADAP DATA NASABAH PERJANJIAN PINJAM MEMINJAM UANG SECARA ON LINE - Rusmini Rusmini; Hj. Yonani Yonani (Justici, 2021)
The emergence of online lending and borrowing facilities through bringing together debtors (loan recipients) with investors / creditors (lenders) through the platform provided by the organizer which can easily be accessed by everyone is a credit facility without collateral to obtain a loan. The Financial Services Authority (OJK) has issued and enforced several regulations on legal protection for consumers in the financial services sector. Legal protection is all efforts to fulfill rights and provide assistance to provide a sense of security to witnesses and / or victims, legal protection of crime victims as part of community protection, can be realized in various forms, such as through the provision of restitution, compensation, medical services, and legal assistance